An overview of various configurations of Luminescent Solar Concentrators for photovoltaic applications - Rafiee, Mehran; Chandra, Subhash; Ahmed, Hind; McCormack, Sarah J. (Optical materials, 2019)
A Luminescent Solar Concentrator (LSC) is an optical waveguide of transparent host material doped with luminophores. LSC technology works by trapping incident solar radiation, converting the spectrum to the wavelength-band of interest and concentrating the light by total internal reflection (TIR) to the edge of the LSC where photovoltaic (PV) solar cell is attached. During the waveguiding process of solar radiation, a considerable proportion of photons are lost through mechanisms such as re-absorption, attenuation, scattering and escape cone losses which decrease the device optical efficiency (OE). In recent decades, various LSC generations with different configurations have been introduced and investigated to mitigate the inherent optical losses and enhance the device performance. Due to the achieved optical improvements, LSC has recently captured a significant growing interest implying its leading role as a low cost and passive technology for enhancing the power conversion efficiency (PCE) of PV systems. In this paper, large and small scale LSCs have been comprehensively reviewed to study the impact of device configuration (such as shape, geometric gain, host material, luminescent species, doping concentration and PV solar cell type) on the LSC loss mechanisms and optical performance. LSC generations are categorised and shortlisted based on their configurations; moreover, their limitations, best performance conditions, best achieved results, and their eligibility for large-scale building integrated PV (BIPV) applications are discussed. •LSCs are comprehensively reviewed.•LSC generations are categorised.•Best achieved results of various generations are discussed.